Korgi: the complete tale ebook - Slade, Christian (Korgi., 2024)
The beloved wordless fantasy graphic novel is now collected in a single epic volume! Fall in love with the wondrous world of Korgi Hollow, packed with thrills, laughs, and exquisitely illustrated animal magic. One of the most adorable comics of our time now arrives in a bookshelf edition for all time. When day breaks in their woodland village, Ivy and her corgi pup, Sprout, have no idea that they’ll soon be swept up in an astonishing adventure! Soon they’ll journey across land, sea, and air, from past to present and beyond, to learn more about themselves, escape the forces of evil, and uncover the ancient mysteries behind their magical world. The sumptuously detailed pen-and-ink drawings of former Disney animator Christian Slade make every page a joy to behold, using the power of “silent comics” to bring every moment wordlessly to life for readers of all ages. What’s more, this deluxe collection includes not only all five Korgi graphic novels but also every bonus short story previously exclusive to comic books. The result is a complete fantasy epic that is truly timeless.